Analisis Bibliometrik Studi Perkembangan Metode Service Quality pada Database Google Scholar Menggunakan Vosviewer (Studi Literatur Tahun 2016 – 2020) - Yeny Rostiany; Evelyn Tjandra (LPPM UBHINUS MALANG, 2022)
This study examines developments with the topic of service quality methods. This study aims to determine: (1) a map of the development of the number of publications on the topic of service quality; (2) find out which scientific articles have the highest number of citations on the topic of service quality; (3) know the map of the development of scientific publications based on keywords. Data collection was carried out by searching the Google Scholar database with the keywords service quality and servqual, with the categories article title, abstract, keywords in the 2016–2020 range. The search results show that there are 907 scientific articles that match the keywords based on the Harzing's Publish or Perish application. The results of this study indicate that the development of publications in 2016-2020 with research topics of service quality methods increases every year, with the highest number of publications in 2020 as many as 287 articles. While the publication that has the highest number of citations is JE Panjaitan, AL Yuliati (2016) with the article title Effect of Service Quality on Customer Satisfaction at JNE Bandung Branch. Map of the development of scientific publications in the VOSViewer application based on the keywords service quality and servqual. Network visualization in the VOSViewer application shows that the agricultural R&D map is divided into nine clusters. Cluster 1 consists of 10 items, Cluster 2 consists of 10 items, Cluster 3 consists of 10 items, Cluster 4 consists of 8 items, Cluster 5 consists of 7 items, Cluster 6 consists of 6 items, Cluster 7 consists of 5 items, and Cluster 8 consists of 3 items, Cluster 9 consists of two items.